Prodrug nanoparticles rationally integrating stroma modification and chemotherapy to treat metastatic pancreatic cancer. (November 2021) - Wang, Liying; Liu, Zimo; Zhou, Quan; Gu, Sufang; Liu, Xiangsheng; Huang, Jianxiang; Jiang, Haiping; Wang, Huifang; Cao, Liping; Sun, Jihong; Shen, Youqing; Meng, Huan; et al.
Abstract: Accumulating evidence suggests that stromal modifications improve chemotherapeutic outcomes in pancreatic ductal adenocarcinoma (PDAC). However, combination regimens of stroma-modifying agents and small-molecule cytotoxic drugs have achieved only limited improvements in the clinic, probably due to unsatisfactory pharmacokinetic profiles and restricted drug distribution in tumors. Here, we developed self-assembled prodrug nanoparticles integrating a stromal reprogramming inducer, calcipotriol (CAL), and a potent chemotherapeutic agent, 7-Ethyl-10-hydroxycamptothecin (SN38), to treat PDAC. While SN38 is conjugated to the block polymer backbone, CAL is loaded into the inner hydrophobic space during polymer self-assembly into nanoparticles. To achieve an efficient drug co-package, a planar and hydrophobic cholesterol domain was introduced to stabilize the hydrophobic CAL. Notably, the blood circulation time of CAL significantly improved as CAL|SN38 nanoparticle (CAL|SN38 NP). In addition, CAL|SN38 NP treatment significantly decreased the expression of N-cadherin, collagen, and fibronectin in tumors, which play critical roles in PDAC metastasis. Potent inhibition of primary tumor growth and vigorous anti-metastasis effects were observed after systemic administration of CAL|SN38 NP to stroma-rich PDAC orthotopic tumor-bearing mice. These findings provide a promising paradigm for developing tailor-made nanoparticles with potent stroma-modification capability to combat metastatic cancer.